Stand-alone Field Trips Based on Geolocation as a Meaningful Source of Learning for Geomatics Students - Meyer, Florian; Théau, Jérôme (Formation et profession)

(untitled) (Centre de recherche interuniversitaire sur la formation et la profession enseignante (CRIFPE), 2022)
The project presented is a prototype of self-guided field trips that rely on the use of a mobile device (tablet) and several of its functions. The article discusses the second iteration of a design-led research approach. The design and research issues were mainly centered on the acceptance of the application and its multiple parameters by the teachers, and on the acceptance by the students of its use for learning purposes. An existing application (TaleBlazer) was selected and adapted. Observed acceptance was measured using the UTAUT model combined with qualitative feedback.